1999
DOI: 10.1002/(sici)1097-4679(199902)55:2<217::aid-jclp9>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of PTSD, schizophrenia, and depression with the MMPI-2

Abstract: This study used 102 male, veteran, psychiatric inpatients to describe patterns of MMPI-2 clinical and content scales that most accurately discriminate among patients diagnosed with PTSD, schizophrenia, and depression. Single scale accuracy classification using scales PK and PS was unacceptably low. Optimally weighted scales, including PK, Sc, BIZ, and ANX, correctly classified 70% of the patients. Suggestions for facilitating the use of formal decision rules are offered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…This is not surprising, however, since axis one of the DSM system is built up of course of illness and symptoms, deliberately excluding personality organization [47], which is considered in axis two [23]. The finding is also consistent with earlier findings of difficulties in demonstrating personality differences even between different main diagnoses [48,49], but it differs from some previous studies using a five-factor model of personality, which have demonstrated differences between people with schizophrenia and healthy controls [1] and between schizophrenia patients and other diagnoses [50].…”
Section: Discussionsupporting
confidence: 82%
“…This is not surprising, however, since axis one of the DSM system is built up of course of illness and symptoms, deliberately excluding personality organization [47], which is considered in axis two [23]. The finding is also consistent with earlier findings of difficulties in demonstrating personality differences even between different main diagnoses [48,49], but it differs from some previous studies using a five-factor model of personality, which have demonstrated differences between people with schizophrenia and healthy controls [1] and between schizophrenia patients and other diagnoses [50].…”
Section: Discussionsupporting
confidence: 82%
“…The MMPI-2 is the most widely used self-report instrument for the assessment of psychopathology and characterological factors and has been used extensively in neuropsychological evaluations, in part, because it is well suited to identify psychological problems that can produce disturbance in concentration and memory (Archer, Buffington-Vollum, Stendy, & Handel, 2006; Camara, Nathan, & Puente, 2000). Multiple studies have demonstrated that the MMPI-2 is sensitive to the presence of PTSD in veteran populations (Greenblatt & Davis, 1999; Keane, Malloy, & Fairbank, 1984; Lyons & Wheeler-Cox, 1999; Penk, Rierdan, Losardo, & Robinowitz, 2005; Wolf et al, 2008). Elevations on Clinical Scales 2, 7, and 8 have found to be associated with PTSD diagnosis in combat veterans and, more recently, the MMPI-2 Restructured Clinical (RC) scales demonstrated improved discriminant validity over the MMPI-2 clinical scales in identifying combat veterans who met criteria for PTSD (Wolf et al, 2008).…”
Section: Minnesota Multiphasic Personality Inventory–2 and Posttrauma...mentioning
confidence: 99%
“…Various modal CS codetypes have been reported in samples of individuals with PTSD ranging from 2-8/8-2 (i.e., Depression and Schizophrenia; Fairbank, Keane, & Malloy, 1983; Keane et al, 1984; Munley, Bains, Bloem, & Busby, 1995; Wilson & Walker, 1990), 7-8/8-7 (i.e., Psychasthenia and Schizophrenia; Albrecht et al, 1994; Litz et al, 1991; Wetter, Baer, Berry, Robison, & Sumpter, 1993), to 6-8/8-6 (i.e., Paranoia and Schizophrenia; Mozley, Miller, Weathers, Beckham, & Feldman, 2005). The 46-item PK scale has demonstrated good sensitivity in the classification of individuals with the disorder (e.g., Greenblatt & Davis, 1999; Keane et al, 1984; Munley et al, 1995). It also appears to contribute incrementally, adding an additional 9% of variance beyond RCd in the prediction of PTSD status in a treatment-seeking inpatient sample; however, these results were not replicated in a compensation-seeking veteran sample (Arbisi, McNulty, & Ben-Porath, 2004).…”
Section: The Mmpi–2 In the Assessment Of Ptsdmentioning
confidence: 99%